Influences of Rapamycin on Retinal Ganglion Cells in Rats with Acute High Intraocular Pressure Through Regulating COX-2: Influences of Rapamycin on Retinal Ganglion Cells - Gao, Yanlin; Fan, Xiaoe; Wan, Bing; Li, Haoqing; Shi, Xueying; Ke, Yifeng (Cellular and Molecular Biology, 2022)
The study aimed to explore the influences of rapamycin on the retinal ganglion cells in rats with acute high intraocular pressure through regulating cyclooxygenase-2 (COX-2). 36 Sprague-Dawley rats were randomly assigned to the normal group (n=12), model group (n=12) and rapamycin group (n=12). The rats in the normal group were normally fed, those in the model group were prepared the model of acute high intraocular pressure and injected with normal saline, and those in the rapamycin group were given rapamycin. At 7 d after the operation, sampling was performed. The expressions of COX-2 and Caspase-3 were detected via immunohistochemistry, and their protein expressions were determined using Western blotting (WB). Quantitative polymerase chain reaction (qPCR) was conducted to measure the messenger ribonucleic acid (mRNA) expression levels, and cell apoptosis was evaluated using terminal deoxynucleotidyltransferase-mediated dUTP nick end labeling (TUNEL) assay. The content of interleukin (IL)-6 and tumor necrosis factor-alpha (TNF-α) was determined via enzyme-linked immunosorbent assay (ELISA). Compared with those in the normal group, the positive expression levels rose substantially in the other two groups, and those in the rapamycin group were notably lower (p<0.05). The relative protein expression levels in the model group and rapamycin group were higher, and the rapamycin group exhibited remarkable decreases (p<0.05). In comparison with the normal group, the other two groups had considerably raised relative mRNA expression levels and those in the rapamycin group were lower (p<0.05). The cells in the model and rapamycin groups had a higher apoptosis rate, and the apoptosis rate of cells in the rapamycin group was lower (p<0.05). Compared with that in the normal group, the content of IL-6 and TNF-α was elevated in the other two groups and their content in the rapamycin group was lower. Rapamycin inhibits COX-2 to repress inflammation and apoptosis, thereby exerting a protective effect on the retinal ganglion cells in rats with acute high intraocular pressure.